Effect of selection for productive traits in broiler male lines on embryo development - GS Schmidt (Revista Brasileira de Ciência Avícola, 2009)
This experiment aimed at evaluating the effect of genetic selection on embryo development of two male broiler lines (LL and LLc). LL line was selected for eight generations for growth, carcass, and reproduction traits. The LLc line was derived from LL line in 1985, and kept under a random mating system with no selection. Fertile eggs were collected and individually weighed for four periods of five consecutive days, with two-week intervals. For every period, a total of 960 eggs/line were identified and separated in four groups of 240 eggs, and then stored for subsequent incubation. At 9 (P9), 11 (P11), 13 (P13), 15 (P15), 17 (P17) and 21 (P21) days of incubation, eggs and embryos were weighed (EmW). Egg weight (EgW) was similar between the two lines. The differences in EmW started to be significant after P15, resulting in a 2.03g difference in hatchling weight, indicating genetic changes of 0.54% by generation, which can be attributed to selection for body weight. The correlation between EgW and EmW started to be significant after P13, and correlations of 0.738 and 0.712 (P21) were observed for LL and LLc, respectively. Hatchling weight corresponded to 71.94 (LL) and 68.96 (LLc) of EgW. The estimated increases in P21 resulting from each 1.0g increase in EgW were 0.73g (LL) and 0.69g (LLc).